Effect of caffeine and other xanthines on liver sinusoidal endothelial cell ultrastructure - Hong Mao; Karolina Szafranska; Larissa Kruse; Christopher Holte; Deanna L. Wolfson; Balpreet Singh Ahluwalia; Cynthia B. Whitchurch; Louise Cole; Glen P. Lockwood; Robin Diekmann; David Le Couteur; Victoria C. Cogger; et al. (Scientific Reports, 2023)
Abstract Xanthines such as caffeine and theobromine are among the most consumed psychoactive stimulants in the world, either as natural components of coffee, tea and chocolate, or as added ingredients. The present study assessed if xanthines affect liver sinusoidal endothelial cells (LSEC). Cultured primary rat LSEC were challenged with xanthines at concentrations typically obtained from normal consumption of xanthine-containing beverages, food or medicines; and at higher concentrations below the in vitro toxic limit. The fenestrated morphology of LSEC were examined with scanning electron and structured illumination microscopy. All xanthine challenges had no toxic effects on LSEC ultrastructure as judged by LSEC fenestration morphology, or function as determined by endocytosis studies. All xanthines in high concentrations (150 μg/mL) increased fenestration frequency but at physiologically relevant concentrations, only theobromine (8 μg/mL) showed an effect. LSEC porosity was influenced only by high caffeine doses which also shifted the fenestration distribution towards smaller pores. Moreover, a dose-dependent increase in fenestration number was observed after caffeine treatment. If these compounds induce similar changes in vivo, age-related reduction of LSEC porosity can be reversed by oral treatment with theobromine or with other xanthines using targeted delivery.